Effect of process parameters on the laser joining of stainless steel with three-dimensional (3-D) printed polymer sheet - Harizam, M.Z.; Tamrin, Khairul Fikri; Nukman, Yusoff; Yusof, Farazila; Sheikh, Nadeem Ahmed (Old City Publishing, 2018)
Dissimilar materials laser joining techniques have gained significance with emerging applications in microelectronics, transportation and aerospace. In the presented study, the laser lap joint of AISI 304 stainless steel and acrylonitrile butadiene styrene (ABS) printed by fused deposition modelling (FDM) with four different raster angle was investigated using continuous wave (CW) fiber laser. All the important parameters such as laser power, joining speed and raster angle are studied with appropriate full factorial design of experiment. Experimental observations indicate that the combination of laser power, joining speed and raster angle results in stronger joint quality. A quantitative analysis using analysis of variance (ANOVA) indicates that joint strength is influenced majorly by 46.46% contribution of laser power. Contribution of welding speed is highest for the heat affected zone (HAZ) width. Moreover, raster angle plays important factor in transferring heat at the joining area. It is also observed that the surface finish of ABS leads to imperfections at the joint where trapped air can lead to void formation.